Nuclear response to supernova neutrino spectra - Tsakstara, V.; Kosmas, T. S.; Sinatkas, J. (HNPS Advances in Nuclear Physics, 2019)
In current probes searching for rare event processes, appropriate nuclear targets are employed (in the COBRA double-beta decay detector the CdZnTe semiconductor is used). In this work the response of such detectors to various low-energy neutrino spectra is explored starting from state-by-state calculations of the neutrino-nucleus reactions cross sections obtained by using the quasi particle random phase approximation (QRPA) based on realistic two-body residual interactions. As a concrete example, we examine the response of 64Zn isotope to low energy supernova neutrinos.